Biofilm-Associated Multidrug-Resistant and Methicillin-Resistant Staphylococcus aureus Infections - Shrestha, Shila; Basnet, Ajaya; Maharjan, Rajendra; Basnet, Bijaya; Joshi, Pramod (Journal of Nepal Health Research Council, 2024)
Background: The ability of Staphylococcus aureus to form biofilms—architectural complexes that cause chronic and recalcitrant infections—along with its notorious variant, methicillin-resistant Staphylococcus aureus (MRSA), leads to multidrug-resistant (MDR) infections that are challenging to treat with antibiotics. This cross-sectional study investigated the prevalence of S. aureus infections in Kanti Children’s Hospital and characterized the antibiograms of MDR, MRSA, and biofilm-forming strains, along with their coexistence.Methods: S. aureus strains were isolated and identified from clinical samples and tested for antibiograms following standard microbiology guidelines. MDR strains were non-susceptible to at least one agent in three antimicrobial categories, whereas MRSA strains were cefoxitin-resistant. The microtiter plate method was used to detect biofilms. Statistical analyses were performed using SPSS version 17.0.Results: S. aureus was detected in 9.0% (11.4-6.6%, 95% Confidence Interval) of 543 samples, primarily from pus (79.6%, 39/49). Children aged 1 to <3 years most commonly contracted infections (30.6%, 15/49), and males (67.4%, 33/49) had twice as many infections as females (32.7%, 16/49). As high as 84.7% (83/98) of strains were penicillin-resistant, while 18.4% (27/147) were aminoglycoside-resistant. MDR accounted for 79.6% (39/49) of all S. aureus infections, while MRSA and biofilm-formers accounted for 67.6% (33/49) and 24.5% (12/49), respectively. Fluoroquinolone resistance in non-MDR-MRSA-biofilm-formers, MDR-MRSA, MDR-biofilm-formers, and MRSA-biofilm-formers was 31.3%, 46.8%, 58.3%, and 60.0%, respectively, while aminoglycoside resistance was 0%, 32.3%, 50.0%, and 45.0%, and penicillin resistance was 87.5%, 85.5%, 100.0%, and 100.0%. Conclusions: MDR-isolates and MRSA caused nearly four-fifths of S. aureus infections. Compared to MDR and MRSA strains, biofilm-formers triggered higher levels of antimicrobial resistance.Keywords: Antibiotics; biofilms; children; resistance; staphylococcus aureus.